SATLINMAS Strategy in Involving Voting Conflicts in Simultaneous Regional Elections for Districts and Cities in East Java Province - Natasya Maura Amanda Febrianti; Nafa Nurhayunda; Umi Zaidah (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
This study analyzes the role and challenges of the Community Protection Unit (Satlinmas) in anticipating conflicts during the 2024 Simultaneous Regional Election voting in East Java. As part of the Satpol PP, Satlinmas plays a role in maintaining security and order at Polling Stations (TPS). The method used is qualitative with a phenomenological approach, through interviews, observations, and document studies. The results of the study show that Satlinmas has carried out training, distributed guidebooks, and coordinated across sectors to prevent conflicts. However, they face obstacles such as limited personnel, weak coordination, and the presence of inactive or unofficial members. Nevertheless, Satlinmas continues to contribute to maintaining election order through cooperation with security forces and community leaders. This study emphasizes the importance of increasing the capacity and professionalism of Satlinmas in order to strengthen the stability of democracy at the local level.